(untitled) (Zoological Records and Reviews, 2022)
Aquatic insects constitute the dominant component of macroinvertebrate communities in most freshwater ecosystems and are among the most widely used bioindicators of water quality, owing to their well-documented differential sensitivity to pollution, their tractable taxonomy, and their integration of environmental conditions over time through their sedentary larval phase. This study presents a systematic assessment of aquatic insect diversity and its relationship with water quality across 48 stream, river, and reservoir sites spanning an urbanisation-to-forest gradient in the Godavari river basin of Telangana and Andhra Pradesh, India, sampled using standardised kick-net and Surber sampler protocols during wet and dry seasons over two years (2019-2021). A total of 284 aquatic insect species from 12 orders and 84 families were documented, dominated by Ephemeroptera (72 species), Trichoptera (64 species), Diptera (58 species), and Plecoptera (38 species). The SIGNAL2 (Stream Invertebrate Grade Number Average Level) biotic index and the EPT (Ephemeroptera-Plecoptera-Trichoptera) richness index together correctly predicted water quality class in 88.4% of sites when validated against physicochemical measurements. Forest stream sites supported the highest EPT richness (mean 48.4 species) and SIGNAL2 scores (mean 6.84), while urban river sites showed the lowest values (mean EPT 8.4; SIGNAL2 3.42). Dissolved oxygen, BOD, and conductivity are the strongest physicochemical predictors of EPT richness. The results validate the applicability of EPT-based bioassessment frameworks to peninsular Indian river systems and provide a calibrated regional reference dataset for water quality monitoring.